Analysis Of The Padang City APBD For The 2018 Fiscal Year: Involution Of Siding To The Public - Krismena Tovalini; Yulia Hanoselina; Yoserizal Yoserizal (Department of Public Administration, 2022)
Within the framework of national development, the budgeting system is an inseparable part of the national development planning system. Planning and budgeting are part of management development that is designed to realize the ideals of national development. Public finance is one of the most critical dimensions to assess the government's partiality to general needs. Many studies have addressed the essential roles of the government budget in trust in government. However, there has been no research that has critically examined the state's alignment with the community through regional budgets. Therefore, this study contributes to the body of knowledge by analyzing local government finance and identifies the weakness of the expenditure. We chose the financial conditions of the city government of Padang in 2018 as the research object. The research was conducted employing qualitative and secondary sources. This study found that the budget is not entirely in favor of the public. Many expenditures have been spent on the program, which does not directly affect society. In sum, Padang city budget has not fully benefited the people of Padang city and sided with them. Our analysis contributes to the study of public finance by strengthening pro-society finance. This study also contributes to the local government in designing and implementing public finance.